High School Coaches Perceptions of Physicians’ Role in the Assessment and Management of Sports-Related Concussive Injury - Williams, Nolan; Sas, Andrew; Madey, Jay; Bodle, Jeff; Scovel, Lauren; Edwards, Jonathan (Frontiers in Neurology, 2012)
Sports concussions are an increasingly recognized common type of mild traumatic brain injury (TBI) that affect athletes of all ages. The need for an increased involvement of trained physicians in the diagnosis and treatment of concussion has become more obvious as the pathophysiology and long-term sequelae of sports concussion are better understood. To date, there has been great variability in the athletic community about the recognition of symptoms, diagnosis, management, and physician role in concussion care. An awareness assessment survey administered to 96 high school coaches in a large metropolitan city demonstrated that 37.5% of responders refer their concussed players to an emergency department after the incident, only 39.5% of responders have a physician available to evaluate their players after a concussion, 71.6% of those who had a physician available sent their players to a sports medicine physician, and none of the responders had their player’s concussion evaluated by a neurologist. Interestingly, 71.8% of responders stated that their players returned to the team with “return to play” guidelines from their physician. This survey has highlighted two important areas where the medical community can better serve the athletic community. Because a concussion is a sport-inflicted injury to the nervous system, it is optimally evaluated and managed by a clinician with relevant training in both clinical neuroscience and sports medicine. Furthermore, all physicians who see patients suffering concussion should be educated in the current recommendations from the Consensus Statement on Concussion and provide return to play instructions that outline a graduated return to play, allowing the athlete to return to the field safely.